TIPOLOGI PERBUATAN MELAWAN HUKUM OLEH PENGUASA DESKRIPSI DOMAIN DAN TAKSONOMIK - Marcus Lukman (Perspektif, 2002)
‘Law and the Leader’ are two concepts which in the process of reciprocal relationship might arise antagonist and protagonist legal problem. Antagonist legal problem will arise U the leader has done illegal act. While, protagonist legal problem will arise if there is a justifiable reason for the act that ethically, morally and legally accountable. Therefore, the further comprehension of the two problems should be examined by domain description and taxonomy typology of the illegal act.